Persistent akathisia masquerading as agitated depression after use of ziprasidone in the treatment of bipolar depression - Penders, Thomas M; Agarwal, Salina; Rohaidy, Rachel (My University, 2013)
There has been increasing recognition that the second-generation antipsychotic drugs can produce extrapyramidal side effects. This case reports the development of severe akathisia in a patient being treated with ziprasidone for bipolar depression. The case illustrates that this symptom can be easily mistaken for worsening agitated depression. Akathisia may produce considerable distress and elevate suicide risk. Such symptoms may persist for weeks and be refractory to discontinuation of the offending agent or to pharmacological interventions commonly used to mitigate this reaction.
Keywords: extrapyramidal; second-generation; affective; antipsychotic; suicide; mood disorder